Pengaruh Beban Pajak Tangguhan Terhadap Manajemen Laba - Rudi Setiadi; Bardjo Sugeng (Fakultas Ekonomi dan Bisnis Universitas Pasundan, 2021)
This study aims to determine the effect of deferred tax expense on earnings management. The population of companies used in this study are food and beverage companies listed on the Indonesia Stock Exchange from 2014-2018. The sample research technique used purposive sampling which resulted in 8 samples of companies. The analytical technique used in this study is the classical assumption test, normality test, autocorrelation test, multicollinearity test, heteroscedasticity test, hypothesis testing, descriptive analysis, associative analysis, correlation analysis, simple regression analysis, and coefficient of determination. Based on the results of the partial study, it shows that deferred tax expense has a significant effect on earnings management with a contribution of 19.3%.